Hydraulic fracturing design considerations, water management challenges and insights for Middle Eastern shale gas reservoirs - Abhijith Suboyin; Md Motiur Rahman; Mohammed Haroun (Energy Reports, 2020)
Water is one of the most important commodities in the world and plays an essential role in the hydrocarbon industry. With increased agricultural production, rapid industrialization, population growth and climate change, the world is facing an extreme water crisis in many regions. Coupled with a surge in energy demand and consumption, this has greatly influenced the hydrocarbon industry. With increasing stress on water resources, it is essential to examine how water is managed within the hydrocarbon industry and devise ways to utilize water more efficiently, especially within water scarce regions such as the Middle East. Augmented by the recent activities in the oil and gas industry, it can be seen that an economical and efficient hydraulic fracturing job has become crucial for the successful development of unconventional reservoirs. However, exploitation of unconventional reservoirs is heavily water-intensive as compared to conventional reservoirs. In this study, a comprehensive investigation that deals with quantification of changes with respect to the variation in prime contributors within a traditional fracture design process is presented. To understand the significance of key design parameters, factors that affect productivity within typical Middle Eastern shale gas reservoirs were analyzed through simple constrained cases. Investigations reveal that parameters such as fracture aperture, natural fracture distribution, fracturing fluid viscosity and Young's modulus are crucial to the overall production and water requirement. Furthermore, an outline for resource management within a traditional fracture design process is presented along with potential challenges for the region. Enhancing existing methodologies and incorporating key parameters highlighted within this study can contribute to the overall value chain. In addition to ultimately assisting in the verification of modern best practices, this investigative approach will create a paradigm for future studies for the region to assist in a simplistic prediction of fracture propagation and associated response to augment water usage.
Keywords: 330; Hydraulic fracturing; Shale gas; Water management; Environment; Middle East